Auditory Stream Segregation with Sinusoidally Amplitude Modulated Tones and Noise in Normal Hearing Adults - Antony P, Jawahar; Barman, Animesh (International Journal of Psychosocial Rehabilitation, 2020)
The study was aimed to know the effect of temporal and spectral variation in sinusoidally amplitude modulated stimuli resulting in auditory stream segregation using objective listening task procedure. Methods: Thirty normal hearing males and females of age range between 18 to 45 years participated in the study. Three carrier stimuli (1 kHz, 4 kHz and broadband) with low (16Hz) and high modulation frequency (256 Hz) were used in the study. The variation in the modulation frequencies increased up to 4 octaves higher for both these frequencies. In the experiment I two tone delay paradigm (AB sequence) and experiment II single tone delay paradigm (B sequence) was used to find the minimum cumulative delay. Results: The results showed no gender difference in the minimum cumulative delay for both the experiments. The results showed that for lower modulation frequency in the tonal carrier stimuli, a variation of about 3-4 octaves higher is required to form stream segregation. Whereas, for higher modulation frequency with the tonal carrier stimuli, relatively smaller modulation hike of about 1-2 octaves is sufficient to elicit the stream perception. However, no stream segregation was noted when the carrier stimuli was a broadband noise. Conclusion: Hence, from this study it is suggested that the temporal variation in the sinusoidally amplitude modulated stimuli alone could not produce any perceptual stream segregation and requires higher modulation frequency with spectral information to detect the stream segregation.